ESRA19-0673 The optimal block for total knee arthroplasty – are we there yet?. (30th August 2019) - Sell, A; Sebastian, MP; Parry, J; Baumber, R
Abstract : Background and aims: We have all struggled with postoperative pain control for total knee arthroplasty (TKA), and the knock-on effect this may have on the patient's recovery and length of stay. Anecdotally with the interspace between the popliteal artery and posterior capsule of the knee (IPACK) block, those anaesthetists who were early adopters have noticed an effect on analgaesic requirement, but does this translate into a better patient journey and earlier discharge from hospital? Methods: After local institutional approval, a retrospective patient chart review was conducted. Inclusion criteria included all adult patients undergoing primary TKA between January and April 2019. We looked at the type of anaesthetic, general or spinal and the regional anaesthetic technique that was used; the only outcome measure was length of stay (LOS). Results: 129 patients were included; 64 had a femoral or proximal adductor canal block (ACB) and IPACK block, 45 had femoral or proximal ACB, 16 had a spinal with local anaesthetic infiltration (LIA), 2 had general anaesthetics with LIA due to failed regional techniques and 2 had epidurals at patient request. Conclusions: This simple retrospective analysis shows a reduction in length of stay when the IPACK is added to a femoral/ACB. We now intend to perform a prospective service evaluation to see if we can identify other areas that can be improved to further reduce the LOS and evaluate patient satisfaction.